Dual-target drugs against Leishmania donovani for potential novel therapeutics - Bora K.; Sarma M.; Kanaujia S.P.; Dubey V.K. (My University, 2025)
Antioxidant defense mechanisms are important for a parasite to overcome oxidative stress and survive within host macrophage cells. Mitochondrial iron superoxide dismutase A (FeSODA) and trypanothione reductase (TR) are critical enzymes in the antioxidant defense mechanism of Leishmania donovani. FeSODA is responsible for neutralizing reactive oxygen species in mitochondria, while TR is responsible for reducing trypanothione, the molecules that help the parasite fight oxidative stress in Leishmania. In this study, we used multitarget ligands to inhibit both the FeSODA and TR enzymes. We combined structure-based drug design using virtual screening approach to find inhibitors against both the targets. The ZINC15 database of biogenic compounds was utilized to extract drugs-like molecules against leishmaniasis. The compounds were screened by standard precision (SP) and extra precision (XP) docking methods. Two compounds, ZINC000008876351 and ZINC000253403245, were selected based on molecular docking based on the binding affinity for both the targets. The screened molecules ZINC000008876351 and ZINC000253403245 showed strong hydrogen bonding with the target proteins according to the Molecular mechanics with generalised Born and surface area solvation (MM-GBSA) techniques. These two compounds were also experimentally investigated on promastigotes stage of L. donovani. Under in vitro condition, the compounds show inhibitory effects on L. donovani promastigotes with IC50 values of 24.82 ± 0.61 µM for ZINC000008876351 and 7.52 ± 0.17 µM for ZINC000253403245. Thus, the screened compounds seem to have good potential as therapeutic candidates for leishmaniasis. © 2023, The Author(s).